2018
DOI: 10.1186/s12954-018-0208-z
|View full text |Cite
|
Sign up to set email alerts
|

The importance of drug checking outside the context of nightlife in Slovenia

Abstract: BackgroundThe main purpose of the research was to evaluate the implementation of the drug checking service in Slovenia and to obtain the opinion of users included in harm reduction programmes for high-risk drug users and of drug users in nightlife settings on drug checking, the reasons for drug checking, and their attitude towards adulterants in the drugs that they use.MethodsThe two final unrepresentative research samples included 102 respondents from harm reduction programmes and 554 respondents from the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 11 publications
(11 reference statements)
5
34
0
Order By: Relevance
“…We can thus argue with confidence that participant‐subsidised pill testing would be an appropriate model in Australia. The high proportion of MDMA use, low levels of supplier trust found in the present sample are comparable with data collected from international nightlife samples .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We can thus argue with confidence that participant‐subsidised pill testing would be an appropriate model in Australia. The high proportion of MDMA use, low levels of supplier trust found in the present sample are comparable with data collected from international nightlife samples .…”
Section: Discussionsupporting
confidence: 84%
“…While prior research has established that pill testing services are endorsed by people who have used MDMA in Australia and overseas , few studies have reported subsequent substance‐using decisions of MDMA users following a pill test result in a festival environment . Therefore, the present study offers an important contribution to a body of research supporting pill testing as a form of harm reduction at music festivals.…”
Section: Discussionmentioning
confidence: 85%
“…This is particularly salient given levels of opioid‐related deaths around the world including in the UK, where over half of DRDs involve opiates . Demand for such community‐based testing services is evident in footfall to Dutch services, with over 12,600 samples submitted in 2018, amongst high risk drug‐using communities in Slovenia, and amongst festival‐goers. For example, an online survey of 851 Australian festival goers found that 85% would use an external, fixed site service if available …”
Section: Drug Safety Testingmentioning
confidence: 99%
“…There are, however, a small number of studies of DCTs use among people who use opioids, including people who inject drugs (PWID). The results of feasibility studies examining expressed willingness to use DCTs among PWID have varied, with willingness ranging across settings from 33 to 90% [ 7 – 9 ]. Feasibility data aside, preliminary findings from an actual fentanyl drug-checking program at a SCS in Vancouver, Canada indicated that a positive fentanyl result was associated with higher odds of dose reduction [ 10 ].…”
Section: Drug Checking Technologiesmentioning
confidence: 99%